Immunopathological Features of Severe Chronic Atopic Keratoconjunctivitis and Effects of Topical Cyclosporine Treatment. (3rd October 2019) - Utine, Canan Asli; Stern, Michael; Akpek, Esen Karamursel
ABSTRACT: Purpose: To assess differential roles of inflammatory cells in pathophysiology of severe atopic keratoconjunctivitis (AKC) and evaluate immunomodulatory effects of topical cyclosporine A (CsA). Methods: A total of 10 patients with severe, steroid-dependent/resistant chronic active AKC were treated using frequent topical CsA 0.05% as monotherapy for 2 months. Conjunctival biopsy specimens before and after treatment were examined using immunohistochemistry. A total of 10 healthy age-matched adults served as the control group. Results: Baseline AKC samples revealed greater cluster of differentiation 4 (CD4), interferon gamma (IFNγ), human leukocyte antigen–D-related (HLA-DR) positive cell densities compared with healthy controls ( P  < 0.05), as well as interleukin (IL)-17 ( P  = 0.08). Topical CsA treatment induced a significant reduction in CD4 and IL-17 expressions ( P  < 0.05); post-treatment levels were same as normals ( P  > 0.05). Despite reduction after treatment ( P  = 0.06), HLA-DR expression remained higher than controls ( P  < 0.05). Conclusions: AKC-related conjunctival inflammation appears to be mediated by delayed hypersensitivity. In this short-term trial, frequent topical CsA improved conjunctival inflammation.